Eco-friendly synthesis of red fluorescent graphene quantum dots from Alstonia scholaris for optoelectronic detection of nitroaromatic compounds - Rachita Newar; Nasrin Sultana; Kalpajit Dutta; Hemen Sarma; Arabinda Baruah (Next Materials)
The synthesis of graphene oxide (GO) using green precursors has garnered significant attention due to its efficiency in various applications. Herein, we have synthesized red fluorescent graphene quantum dots (RGQDs) using GO and a bio-precursor, Alstonia scholaris (AS) leaf extract, as capping and stabilizing agents. AS leaves are rich in polyphenols, which can serve as an effective bio-reagent for the synthesis of RGQDs. For the synthesis of RGQDs, we have adopted a simple hydrothermal approach. After the successful synthesis of the material, we developed a fluorometric and electrical sensing platform for detecting picric acid (PA) and para-nitrophenol (PnPh). Both PA and PnPh are hazardous environmental pollutants. The RGQDs exhibited exceptional sensitivity and selectivity towards PA and PnPh, with optical sensing limits of 0.288 µM and 0.322 µM, respectively. Additionally, a biodegradable and cost-effective electrical sensor was also fabricated for detecting the same, achieving a lower detection limit of 1.17 µM and 0.71 µM for PA and PnPh, respectively, which exemplifies the superior analytical precision and sensitivity of the sensor. In addition to developing the sensing platforms, we investigated the antibacterial activity of RGQDs against both Staphylococcus aureus (a Gram-positive bacterium) and Escherichia coli (a Gram-negative bacterium). Antibacterial activity was evaluated through standard microbiological analysis, including minimum inhibitory concentration (MIC) measurements. The MIC estimations against S. aureus and E. coli are 24.76 ± 1.53 µg/mL-1 and 21.966 ± 1.104 µg/mL-1, respectively. The RGQDs demonstrated potent antibacterial effects, with significant growth inhibition capacity for both bacterial strains. In summary, this work presents a novel method for synthesizing RGQDs with dual-mode detection capabilities and significant antibacterial properties.